Interaksi Sosial Keagamaan Antara Siswa Muslim Dan Siswa Katolik (Studi Kasus SD Slamet Riyadi Kebon Kangkung, Kota Bandung) - Setio Qadrian Perdana (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2018)
SD Ignatius Slamet Riyadi is a school under the auspices of the Foundation of the Holy Cross. Students in the school consist of Catholic, Christian, Buddhist and Islamic students. There are more Catholic students than Muslim students. Muslim students and non-Muslim students interact in the school environment. The purpose of this study to answer the problems are (1) How the religious life of Muslim students SD Slamet Riyadi? (2) How is the religious social behavior of different religious students in SD Slamaet Riyadi? (3) How is the friendship between Muslim student and SD Katama Slamaet Riyadi?The location of this research is SD Ignatius Slamet Riyadi Kebon Kangkung Bandung. Research subjects are Muslim students, while research sources consist of classroom teachers, principals and parents. Data collection techniques used are observation, interview and documentation. Data analysis is data reduction, data presentation and conclusion drawing or verification.The results showed that the form of interaction between Muslim students and Catholic students through discussions, extracurricular activities, breaks in the school cafeteria and competition in academic terms. Social behavior of Muslim students feel comfortable in interacting with classmates and friends in one school. The behavior of Muslim students who are polite and courteous enough to maintain good relationships. The religious life of Muslim students is strongly influenced by culture and learning in Catholic schools. One of the patterns of worship is to pray very much to imitate the catholic worship of praying with the use of hand symbols dikepal and Indonesian language.The conclusion that can be drawn from this research is: the form of interaction between students in SD Slamet Riyadi divided form on the interaction of friendship school, in class and at home with parents. Factors that affect the occurrence of interaction between Muslim students with Catholic students SD Slamet Riyadi is the education of tolerance and school culture are disciplined and comfortable to follow activities together. Education Tolerance is implemented through teacher dialogue both when learning activities. The existence of different religious students is acceptable in the majority Catholic environment, so Muslim students are well received. SD Slamet Riyadi too, has educated students from various religions, learning patterns and curriculum set making these students feel comfortable studying in Catholic schools.